Randomized, placebo-controlled, double-blinded study of prophylactic cranberries use in women with recurrent uncomplicated cystitis - Tsiakoulias, Eleftherios; Gravas, Stavros; Hadjichristodoulou, Christos; Oikonomou, Katerina G; Kyritsi, Maria; Dadouli, Katerina; Matziri, Alexia; Kola, Konstantina; Vacthsioli, Evangelia; Tsiakoulia, Marianna; Gianniou, Michaela; Tzortzis, Vassilios (My University, 2024)
Τhe adherence of p-fimbriated Escherichia coli (E. coli) to urothelial cells leading to recurrent urinary tract infections (rUTIs) may be prevented by proanthocyanidins (PACs) contained in American cranberries.
Keywords: Recurrent urinary tract infections; Cranberry; PACs; Proanthocyanidins